PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN FLIP BOOK TERHADAP HASIL BELAJAR DITINJAU DARI GAYA BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENGANTAR EKONOMI DAN BISNIS (STUDI EKSPERIMEN PADA PESERTA DIDIK KELAS X SMK NEGERI 1 KARANGANY - Muslikhah, Riana Isti; M,Stats, Siswandari; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2016)
The objectives of this research are to investigate: (1) the difference of effect between the Flip Book-assisted Quantum Teaching model and the Expository learning model on the learning result in the subject matter of Introduction to Economics and Business; (2) the difference of effect among the visual, auditory, and kinesthetic learning styles on the learning result in the subject matter of Introduction to Economics and Business; and (3) the interaction of effect of the learning models and the learning styles to the learning result in the subject matter of Introduction to Economics and Business.            This research used the experimental research method with the factorial design of 2x3. The samples of research were taken by using the simple random sampling technique. The data of research were gathered through test of learning result on the subject matter of Introduction to Economics and Business and questionnaire of learning styles. The proposed hypotheses of research were analyzed by using the two-way analysis of variance (ANOVA) continued with multiple-comparison test.            The results of research are as follows: (1) there is a difference of effect between the Flip Book-assisted Quantum Teaching learning model and the Expository learning model on the learning result in the subject matter of Introduction to Economics and Business; (2) there is a difference of effect among the visual, auditory, and kinesthetic learning styles on the learning result in the subject matter of Introduction to Economics and Business; and (3) there is an interaction of effect of the learning models and the learning styles to the learning result in the subject matter of Introduction to Economics and Business.Keyword:Quantum teaching,  flip book, learning styles, expository, and learning result